Cerebral oxidative stress, inflammation and apoptosis induced by intermittent hypoxia: a systematic review and meta-analysis of rodent data - Bayan El Amine; Joey Fournier; Mélanie Minoves; Sébastien Baillieul; Frédéric Roche; Nathalie Perek; Jean-Louis Pépin; Renaud Tamisier; Charles Khouri; Claire Rome; Anne Briançon-Marjollet (European Respiratory Review)
Obstructive sleep apnoea (OSA) contributes to cerebrovascular diseases and cognitive decline. Preclinical studies support the deleterious impact on the brain of intermittent hypoxia (IH), one of the main components of OSA, but heterogeneity in rodent species and brain regions studied, or induced by IH paradigms, can challenge interpretation of the studies. Hence, we conducted a systematic review and meta-analysis to evaluate the impact of IH on rodent brain oxidative stress, inflammation, apoptosis and the expression of brain-derived neurotrophic factor (BDNF) and hypoxia-inducible factor 1 (HIF-1). PubMed and Web of Science searches identified 663 articles related to IH exposure, of which 60 were included. The examined outcomes were oxidative stress, inflammation, apoptosis, HIF-1 or BDNF in brains. Standardised mean difference was used to compare studies. Metaregressions were performed to clarify the impact of IH exposure parameters, rodent characteristics or cerebral localisation on these outcomes. IH-induced oxidative stress (increased malondialdehyde (MDA) and NADPH oxidase (NOX) and decreased superoxide dismutase), increased inflammation (tumour necrosis factor-α, NF-κB and inducible nitric oxide synthase), HIF-1 and apoptosis evaluated by terminal deoxynucleotidyl transferase dUTP nick-end labelling and cleaved caspase-3. In contrast, B-cell lymphoma 2 (BCL2) and BDNF expression were not significantly modified. Metaregressions showed that MDA, NOX and BDNF were associated with determinants of IH cycles (inspired oxygen fraction and duration of hypoxia) and some parameters depended on localisation. Rodent characteristics had little impact on the outcomes. Our meta-analysis robustly establishes that IH, independently of other confounders, has a strong effect on the brain by inducing oxidative stress, inflammation and apoptosis in rodent models. Our findings support the interest of considering and treating cerebral consequences of OSA in clinical practice.